Pengembangan dan Evaluasi Bahan Ajar Elektronik Berbasis iSpring Suite untuk Pembelajaran Informatika - Siti Hawani; Gusnita Darmawati; Firdaus Annas; Yulifda Elin Yuspita (Yayasan Lembaga Studi Makwa, 2025)
Informatics learning at MTsN 6 Agam still faces challenges related to the limited availability of innovative, technology-based instructional materials and the dominance of conventional teaching methods, which negatively affect students’ learning interest and conceptual understanding. These conditions indicate the need for the development of interactive electronic teaching materials that are aligned with students’ characteristics. This study aims to develop electronic teaching materials based on iSpring Suite that are valid, practical, and effective for Grade VIII Informatics learning at MTsN 6 Agam. The study employed a Research and Development (R&D) approach using the 4D development model, consisting of the Define, Design, Develop, and Disseminate stages. The research subjects included media experts, subject-matter experts, Informatics teachers, and Grade VIII students. Data were collected through validity, practicality, and effectiveness questionnaires. The results indicate that the developed electronic teaching materials are valid, with an average validity score of 0.84, highly practical with an average practicality score of 0.94, and effective for learning implementation with an effectiveness score of 0.91. These findings demonstrate that electronic teaching materials based on iSpring Suite are suitable for use in Informatics learning and are capable of enhancing students’ motivation and learning engagement. The contribution of this study lies in providing empirical evidence on the development of application-based electronic teaching materials integrated with interactive multimedia at the madrasah tsanawiyah level, thereby enriching research on Informatics learning media development in the context of digital education. Abstrak Pembelajaran Informatika di MTsN 6 Agam masih menghadapi kendala berupa keterbatasan bahan ajar inovatif berbasis teknologi serta dominasi metode pembelajaran konvensional yang berdampak pada rendahnya minat dan pemahaman siswa. Kondisi tersebut menunjukkan perlunya pengembangan bahan ajar elektronik yang interaktif dan sesuai dengan karakteristik peserta didik. Penelitian ini bertujuan untuk mengembangkan bahan ajar elektronik berbasis iSpring Suite yang valid, praktis, dan efektif pada mata pelajaran Informatika kelas VIII MTsN 6 Agam. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan 4D yang meliputi tahap Define, Design, Develop, dan Disseminate. Subjek penelitian melibatkan ahli media, ahli materi, guru Informatika, serta siswa kelas VIII. Data dikumpulkan melalui angket validitas, praktikalitas, dan efektivitas. Hasil penelitian menunjukkan bahwa bahan ajar elektronik yang dikembangkan dinyatakan valid dengan nilai rata-rata 0,84, memiliki tingkat praktikalitas sangat tinggi dengan nilai rata-rata 0,94, serta efektif digunakan dalam pembelajaran dengan nilai efektivitas sebesar 0,91. Temuan ini menunjukkan bahwa bahan ajar elektronik berbasis iSpring Suite layak digunakan sebagai media pembelajaran Informatika dan mampu meningkatkan motivasi serta keterlibatan belajar siswa. Kontribusi penelitian ini terletak pada penyediaan bukti empiris pengembangan bahan ajar elektronik berbasis aplikasi yang terintegrasi dengan multimedia interaktif pada jenjang madrasah tsanawiyah, serta memperkaya kajian penelitian pengembangan media pembelajaran Informatika di era pembelajaran digital.